2014
DOI: 10.1080/0144929x.2014.983979
|View full text |Cite
|
Sign up to set email alerts
|

‘Can I afford to help?’ How affordances of communication modalities guide bystanders' helping intentions towards harassment on social network sites

Abstract: When bystanders want to help victims of harassment on social network sites, they can be guided by the affordances of different communication modalities in order to make a communicative choice. Elaborating on the data of a previous experimental study with 453 adolescents, we compared bystanders' behavioural intentions to help the victim according to their 'mediacy' (via communication technologies (CT) or face-to-face) and their 'privacy' (in public or in private). Furthermore, we investigated whether the contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 44 publications
5
41
0
2
Order By: Relevance
“…Affordances refer to the qualities or properties of an object that describe its possible uses or clarify how it can or should be used (Gibson, ). Scholars (e.g., Bastiaensens et al, ) have proposed that the qualities of different modes of communication can help to understand the implications of different communication technologies such as mobile phones (Reid & Reid, 2007) and social media (Boyd, ; Ellison & Vitak, ; Treem & Leonardi, ). For instance, Treem and Leonardi (2012) listed four affordances that differentiate social media from other forms of online and face‐to‐face communication: visibility, persistence, editability, and association.…”
Section: The Present Studymentioning
confidence: 99%
“…Affordances refer to the qualities or properties of an object that describe its possible uses or clarify how it can or should be used (Gibson, ). Scholars (e.g., Bastiaensens et al, ) have proposed that the qualities of different modes of communication can help to understand the implications of different communication technologies such as mobile phones (Reid & Reid, 2007) and social media (Boyd, ; Ellison & Vitak, ; Treem & Leonardi, ). For instance, Treem and Leonardi (2012) listed four affordances that differentiate social media from other forms of online and face‐to‐face communication: visibility, persistence, editability, and association.…”
Section: The Present Studymentioning
confidence: 99%
“…They found that the severity of a bullying incident (i.e., the level of threats and insults used) predicted whether bystanders noticed a victim's emergency as well as whether they felt responsible for intervening. Bastiaensens et al (2014Bastiaensens et al ( , 2015 and Patterson et al (2017a) provided evidence that more severe cyberbullying induced higher intentions of intervening among bystanders. Bastiaensens et al (2014) also showed that these behavioral intentions were better explained by bystanders' perceived severity as compared to only drawing on an incident's "objective" severity.…”
Section: Incident Severity and Bystander Interventions In Cyberbullyingmentioning
confidence: 99%
“…More specifically, we investigate how the severity of an incident predicts bystander interventions. Previous researchers have shown that bystanders are more likely to intervene in more severe incidents than in less severe ones (Bastiaensens et al, , 2015Kazerooni, Taylor, Bazarova, & Whitlock, 2018;Obermaier et al, 2016;Patterson, Allan, & Cross, 2017a,b). Researchers usually operationalize differences in incident severity as either an "objective" characteristic of different bullying incidents (e.g., Kazerooni et al, 2018;Obermaier et al, 2016) or as differing perceptions of the severity of the same incident (e.g., Patterson et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, an onlooker of more severe acts of bullying may experience greater shame for not intervening in a positive manner (Bandura 1986;Cappadocia et al 2012). Consistent with this line of thinking, some studies report that young people tend to offer help for more as opposed to less severe cyberbullying (Bastiaensens et al 2014(Bastiaensens et al , 2015Obermaier et al 2016) and traditional bullying (Cappadocia et al 2012;Forsberg et al 2018). On the other hand, research has shown that many young people are aware that siding with victims runs the risk of becoming targeted by the bullies (Boulton 2013).…”
mentioning
confidence: 96%
“…It is these characteristics that allow young people to choose how to respond and control their self-presentation online (Madell and Muncer 2007;Valkenburg and Peter 2011). This perceived control online allows bystanders to positively intervene through communication technology in a private manner (Bastiaensens et al 2015;Wong-Lo and Bullock 2014).…”
mentioning
confidence: 99%